Study on the Factors Influencing Residential Location Choice of the Garments Workers of Mirpur, Dhaka City - Shawal, Shammi; Ferdous, Jannatul (International Journal of Chemical and Process Engineering Research, 2014)
Bangladesh is a developing country with huge population and huge scarcity of resources. Its economy is largely dependent on ready-mate-garment industry. So garments industries as well as garments workers are very much important for our economy. Dhaka being the capital city, a large number of garment factories is situated here. But the majority of garment workers earn less than the living wage, which is the minimum requirement to provide a family with food, shelter and education. They can hardly find a suitable residence for them and are compelled to live in congested, unhygienic and sub-human condition. The development of a country is not possible by only developing the middle and upper class people depriving the lower class who occupy a major part of the economy. So, it’s the need of the day to solve the problems of the housing condition of the garments workers. Therefore, this study emphasizes on the factors influencing residential location choice of the garment workers of Dhaka city. The target group is the residents of Mirpur 1. House rent, availability of utility facilities, monthly household income, distance from workplace, social security, dependence on family decision, size of dwelling unit, communal living, availability of community facilities - these have been pointed out as important factors in residential location choice of the garment workers by questionnaire survey. The study also investigated the priority among the pointed factors so that it could help the policy makers and developers to take any types of housing development project for the workers. If we can ensure a better residence and better facilities for them, their potentiality will increase and in the long run we can reap greater benefit from them.